KEMAMPUAN MAHASISWA CALON GURU DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN DAN BAHAN AJAR MATEMATIKA BERBASIS PROBLEM BASED LEARNING (PBL) - Monike Audya Sitepu, Rikky Vinansius Sihotang (Pondok Pesantren Baitul Qur`an Sambas, 2024)
This research aims to develop learning media based on Problem Based Learning (PBL) to improve students' abilities in solving mathematical problems. This research uses a Research and Development (R&D) approach with four stages: definition, design, development and dissemination. The results of this research show that PBL-based E-LKPD learning media can improve students' analysis and synthesis skills in solving complex mathematical problems. Apart from that, this media can also increase students' motivation and interest in learning as well as learning effectiveness. In synthesis, this research shows that the development of PBL-based learning media can help improve students' abilities in critical thinking and analysis and improve learning outcomes.